BERKOMUNIKASI EFEKTIF DENGAN KALIMAT EFEKTIF DALAM BAHASA INDONESIA - Parto, Parto (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
The most effective communication media is language. However, not all uses of language can produce effective communication. Effective communication can only be done when there is an understanding between the communicator and the communicant. This means that language understanding between communicators and communicants is a demand in effective communication (Kemendikbud, 2013). In such languages it is necessary to use effective sentences. Therefore, in effective communication effective sentences. In other words, effective communication can only be achieved by using effective sentences. In this paper explained about communication, effective communication, and effective sentences in Indonesian.